PLC–HMI integration for water tank control and monitoring system with control performance evaluation industrial - Armin Armin; Ihsan Ihsan; Muhammad Bahit; Nur Yanti; Mikail Eko Prasetyo Widagda; Ferdy Kahandanie; Endang Sri Apriana; Noprianto Noprianto (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2026)
This research designs and implements a water tank control and monitoring system based on a Programmable Logic Controller (PLC) integrated with a Human-Machine Interface (HMI) to enhance operational efficiency and reliability in an industrial environment. The system is built using a Schneider M221 PLC and analogue modules, with a level transmitter as the primary sensor for level control, and flow and temperature transmitters to complement process condition information. The control logic is implemented using ladder logic in EcoStruxure Machine Expert. At the same time, the HMI interface is developed in Vijeo Designer for real-time visualization, setpoint adjustment, and pump status monitoring and alarms. System performance is evaluated through hardware functional testing (power supply, relay, pump) and sensor testing based on 4–20 mA signals converted using a scaling Equation. To further assess control performance, a dynamic response test, more specifically, a step response, was employed. From a starting level of 10 cm to a setpoint of 25 cm, data was recorded every two seconds. The study includes critical performance metrics such as rising time, settling time (within ±5% tolerance), overshoot, and steady-state error. With a rising time of 9.22 seconds, a settling time of 14 seconds, an overshoot of 2.0%, and no steady-state error, the data showed that the system steadily approached the intended setpoint. These findings demonstrate that integrating a PLC and HMI provides reliable water tank level monitoring and control and is suitable for use as an automation solution in industrial settings.